The Relationship Between Occupational Hazards and Oral Health in Different Professions - Almustafa, Nawaf Mohammed; Albulayhid, Ahad Nasser; Alshahrani, Aidel Abdullah; Albeirouti, Soha Hassan; Aldosari, Mohammed Nasser; Alsaud, Muneera Mohammed; Albawardi, Khalid Waleed; Aloriny, Tawfeeg Saleh (Journal of Posthumanism, 2025)
It is well known that occupational hazards impact general health but little is known about how they affect oral health. Risks associated with various occupations include chemical exposure, ergonomic strain, stress-induced bruxism and dietary practices that affect oral health. Heavy metals and industrial chemicals such as lead, sulfuric acid and mercury can cause mucosal lesions, systemic toxicity and dental erosion. Bruxism, TMJ disorders, and dry mouth are more common in high-stress occupations like law enforcement and healthcare, which can result in gum disease and enamel wear. The risks of xerostomia and disturbed oral hygiene habits are increased for shift workers and people exposed to high temperatures, which exacerbates oral health problems. Additionally, exposure to pesticides in agriculture is associated with a higher risk of oral cancer and burning mouth syndrome while airborne pollutants like silica dust and welding fumes increase vulnerability to oral infections and precancerous lesions. First responders and healthcare professionals are also more vulnerable to infectious disease transmission that compromises oral health. The relationship between oral health and occupational hazards in various professions is examined in this literature review, which also identifies important risk factors, their effects and possible preventive measures. For workers in a variety of industries to have better oral and general health outcomes, these risks must be addressed.